The quasi-stationary approximation for the Stefan problem with a convective boundary condition - A. D. Solomon; D. G. Wilson; V. Alexiades (International Journal of Mathematics and Mathematical Sciences)
We show that the solution to the Stefan problem with a convective boundary condition tends to the quasi-stationary approximation as the specific heat tends to zero. Additional properties of the approximation are given, and some examples are presented.